اﻟﺗﻣﺛﯾل اﻟﻣﻌرﻓﻲ وﻋﻼﻗﺗﮫ ﺑﺄﺳﺎﻟﯾب اﻟﺗﻌﻠم واﻟﺗﻔﻛﯾر ﻟدى طﻠﺑﺔ اﻟﻣرﺣﻠﺔ اﻹﻋدادﯾﺔ (Journal of the College of Education for Women, 2019)
The recent researches aim to discuss the following items : 1. Knowing of the level of cognitive representation. 2. knowing of the premium style of general learning and thinking. 3. knowing the differences in cognitive representation and preferring treatment style as well legislation thinking in both the variable specialist and sex. 4. Discover the relation between the cognitive representation on learning and thinking. For the purpose of inspection the aims of research the two researches used the scale of cognitive representation in which prepared by her self, the scale include the Iraqi environment for secondary school students and syrenberch scale to be adapt with the stage. Have been applied to these three tools on a sample of students from the secondary school of Baghdad was contingent "200" student "male and female". In order to analyze the results, the two researchers used group of statistical methods as a second option for one selected group and independent group of study, analyze the bilateral contrast. analyze the multiple grading. The results is as follow: 1. Measure the level of cognitive representation at the students of fourth secondary classes which is good. 2. The female is better than male in the cognitive representation. 3. There is no difference in representation according to specialist variable also no reaction had been shown. 4. Student was discriminated in using the methods of using separation treatment and legislation thinking. 5. The results from this case having relation between 11 types of learning of learning methods and thinking. As a result, the researchers reach to some conclusion and recommendations in the field of study, useful if used in such future subjects.